ANALISIS REAKSI PASAR TERHADAP PECAHNYA PERANG ANTARA IRAN DAN ISRAEL: STUDI KASUS PADA PERUSAHAAN SEKTOR ENERGI DI WILAYAH ASEAN - Ratuela, Hillary Sharon Patricia; Saearng, Ivonne S.; Rumokoy, Lawren J. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Shifts in geopolitical dynamics have the potential to impact stock returns, influence on investors, and decision-making by economic policymakers. One event that reflects this dynamic is the outbreak of war between Iran and Israel, which has created uncertainty and triggered market reactions, particularly among energy companies in the ASEAN region. This ongoing tension has a direct impact on the stability of the Middle East region, as Iran is one of the world's leading oil exporters, and the region is heavily reliant on energy imports. It has been demonstrated that fluctuations in the supply chain or prices can exert a direct influence on the value of energy companies listed on the stock market. The objective of this study is to analyze the differences in abnormal returns, trading volume activity, and market capitalization before and after the outbreak of war between Iran and Israel. The research sample was selected using purposive sampling, with 50 energy sector companies listed on the stock exchanges of five ASEAN member countries—Indonesia, Singapore, Malaysia, Thailand, and the Philippines—selected from the top 10 market capitalizations per country. The methodology employed was an event study approach, which entailed a 14-day observation period preceding and following the event. A statistical analysis was conducted using the paired sample t-test via SPSS. The findings of the study suggest that, among the three variables examined, only abnormal returns exhibited a substantial discrepancy before and after the occurrence. This finding indicates that the market exhibited a substantial response in terms of stock returns; however, this response was not accompanied by significant alterations in trading volume or market capitalization.